Surgical ventricular reconstruction for ischemic cardiomyopathy—a systematic review and meta-analysis of 7,685 patients - Ferrell, Brandon E.; Jimenez, Diana C.; Ahmad, Danial; Malkani, Kabir; Rosen, Jake L.; Gaw, Gabriel; Plestis, Konstadinos A.; Guy, T. Sloane; Massey, H. Todd; Tchantchaleishvili, Vakhtang (Annals of Cardiothoracic Surgery, 2022)
Background: Surgical ventricular reconstruction (SVR) has been used to control adverse ventricular remodeling and improve cardiac function in ischemic cardiomyopathy. The purpose of this systematic review and meta-analysis was to collect and analyze all available evidence on the utilization and efficacy of SVR. Methods: An electronic database search was performed to identify all retrospective and prospective studies on SVR for ischemic cardiomyopathy in the English literature from 2000 through 2020. A total of 92 articles with a collective 7,685 patients undergoing SVR were included in the final analysis. Results: The mean patient age was 61 years (95% CI: 59–63) and 80% (78–82%) were male. Congestive heart failure was present in 66% (54–78%) and angina in 58% (45–70%). Concomitant coronary artery bypass grafting was undertaken in 92% (90–93%) while 21% (18–24%) underwent mitral valve repair. Pre vs. post-SVR, significant improvement was seen in left ventricular ejection fraction (LVEF) [29.9% (28.8–31.2%) vs. 40.9% (39.4–42.4%), P